Efficient data access for Open Modeling Interface (OpenMI)components - Bulatewicz, Tom; Andresen, Daniel (My University, 2011)
Data management for linked (or coupled) simulation models can be a challenging task when deploying to grid environments. In cases where the linked models conform to a standard interface for data input and output, generalpurpose data providers can be used to supply data to the models from online sources, reducing the complexity of the deployment. We have developed a data provider component that conforms to the Open Modeling Interface (OpenMI) that is suitable for use on computational grids. Through the application of three techniques, caching, prefetching, and pipelining, the component efficiently retrieves data from standards-based web services and delivers the data to OpenMI-compliant models. Each technique resulted in varying performance improvements both within a single simulation and across multiple simulations concurrently executing on a cluster. In this paper we report on the design of the component and the evaluation of its performance.
Keywords: OpenMI; Data access; Web services; Modeling and simulation